Membranes of Polymer of Intrinsic Microporosity PIM-1 for Gas Separation: Modification Strategies and Meta-Analysis - Qiu, Boya; Gao, Yong; Gorgojo, Patricia; Fan, Xiaolei (Nano-Micro Letters, 2025)
Polymers of intrinsic microporosity (PIMs) have received considerable attention for making high-performance membranes for carbon dioxide separation over the last two decades, owing to their highly permeable porous structures. However, challenges regarding its relatively low selectivity, physical aging, and plasticisation impede relevant industrial adoptions for gas separation. To address these issues, several strategies including chain modification, post-modification, blending with other polymers, and the addition of fillers, have been developed and explored. PIM-1 is the most investigated PIMs, and hence here we review the state-of-the-arts of the modification strategies of PIM-1 critically and discuss the progress achieved for addressing the aforementioned challenges via meta-analysis. Additionally, the development of PIM-1-based thin film composite membranes is commented as well, shedding light on their potential in industrial gas separation. We hope that the review can be a timely snapshot of the relevant state-of-the-arts of PIMs guiding future design and optimisation of PIMs-based membranes for enhanced performance towards a higher technology readiness level for practical applications. Highlights: 1 Critical review of the polymers of intrinsic microporosity (PIM)-1-based membranes for applications in selective CO2 separation. 2 State-of-the-art modification strategies for PIM-1 are thoroughly compared via meta-analysis. 3 Key perspectives for progressing PIM-1 thin film membranes towards practical applications are suggested.